Quantifying oxygen distortions in lithium-rich transition-metal-oxide cathodes using ABF STEM - Liberti, E; Lozano, JG; Pérez Osorio, MA; Roberts, MR; Bruce, PG; Kirkland, AI (Elsevier, 2019)
Lithium-rich cathodes can store excess charge beyond the transition metal redox capacity by participation of oxygen in reversible anionic redox reactions. Although these processes are crucial for achieving high energy densities, their structural origins are not yet fully understood. Here, we explore the use of annular bright-field (ABF) imaging in scanning transmission electron microscopy (STEM) to measure oxygen distortions in charged Li1.2Ni0.2Mn0.6O2. We show that ABF STEM data can provide positional accuracies below 20 pm but this is restricted to cases where no specimen mistilt is present, and only for a range of thicknesses above 3.5 nm. The reliability of these measurements is compromised even when the experimental and post-processing designs are optimised for accuracy and precision, indicating that extreme care must be taken when attempting to quantify distortions in these materials.